Can liberal egalitarians protect the occupational freedom of the economically talented?. Issue 6 (2nd November 2018) - Mazor, Joseph
Abstract : This article considers and ultimately rejects three prominent liberal egalitarian strategies for safeguarding the occupational freedom of the economically talented. First, Dworkinian concerns regarding the envy of the talented for the less talented are shown to be insufficient to rule out occupationally coercive taxation. Second, Rawlsian arguments about the priority of basic liberties in general and freedom of occupation in particular are shown to be unsuccessful, primarily because Rawls lacks the theoretical resources to protect freedom of occupation as a basic liberty. Finally, concerns about the practical difficulty and moral undesirability of gathering the information necessary to implement occupationally coercive taxation are shown to be insufficient to rule out such taxation. The aim of the article is not to lead liberal egalitarians to reject freedom of occupation. Rather, the aim is to highlight the difficulties in protecting freedom of occupation and to motivate work on alternative liberal egalitarian strategies for safeguarding this important economic liberty. At the end of the article, a hypothesis is put forward for why occupationally coercive taxation should be rejected that appeals to the prohibition on using people as means.